Effect of Apolipoprotein E on Biomarkers of Amyloid Load and Neuronal Pathology in Alzheimer Disease - Vemuri, Prashanthi (2010)
OBJECTIVE: To study the effect of apolipoprotein E ε4 status on biomarkers of neurodegeneration (atrophy on magnetic resonance imaging [MRI]), neuronal injury (cerebrospinal fluid [CSF] t-tau), and brain Aβ amyloid load (CSF Aβ(1–42)) in cognitively normal subjects (CN), amnestic subjects with mild cognitive impairment (aMCI), and patients with Alzheimer disease (AD). METHODS: We included all 399 subjects (109 CN, 192 aMCI, 98 AD) from the Alzheimer's Disease Neuroimaging Initiative study with baseline CSF and MRI scans. Structural Abnormality Index (STAND) scores, which reflect the degree of AD-like anatomic features on MRI, were computed for each subject. RESULTS: A clear ε4 allele dose effect was seen on CSF Aβ(1–42) levels within each clinical group. In addition, the proportion of the variability in Aβ(1–42) levels explained by APOE ε4 dose was significantly greater than the proportion of the variability explained by clinical diagnosis. On the other hand, the proportion of the variability in CSF t-tau and MRI atrophy explained by clinical diagnosis was greater than the proportion of the variability explained by APOE ε4 dose; however, this effect was only significant for STAND scores. INTERPRETATION: Low CSF Aβ(1–42) (surrogate for Aβ amyloid load) is more closely linked to the presence of APOE ε4 than to clinical status. In contrast, MRI atrophy (surrogate for neurodegeneration) is closely linked with cognitive impairment, whereas its association with APOE ε4 is weaker. The data in this paper support a model of AD in which CSF Aβ(1–42) is the earliest of the 3 biomarkers examined to become abnormal in both APOE carriers and noncarriers.